STUDY ON THE Ph INFLUENCE ON SURFACE MICROHARDNESS OF SOME REPAIR MATERIALS USED IN ENDODONTICS - Liana Aminov; Mihaela Salceanu; T.Hamburda; Anca Melian; Dana Cristiana Maxim; Maria Vataman (Romanian Society of Oral Rehabilitation, 2013)
Introduction The irrigating solutions used in endodontic therapy have different pH values and different chemical properties that have sometimes been found to adversely affect the physical and chemical characteristics of reparing materials. These materials are used mainly in areas of inflamed tissue, with a lower pH. Aim of the study To evaluate the changes in the hardness of two dental materials depending on pH variations and to determine which of the additives they are combined with gives them greater stability to pH variations. Material and methods The changes in surface microhardness (Vickers microhardness) of two repair materials: Grey MTA (Dentsply Tulsa Dental, USA) and BioAggregate (Innovative BioCeramix Inc., Vancouver, Canada), mixed with four different vehicles (distilled water, physiological saline, lidocaine and calcium chloride) and subsequently subjected to different environmental pH values. Vickers microhardness of each specimen was measured by means of Emcotest M1C 010 model. Results The analysis of the average surface hardness of the two repair materials showed a significant increase in hardness at high pH (pH = 7) and higher values for BioAggregate as compared with MTA. Conclusions Ph variations of the environment in which biomaterials are setting reduce their microhardness and surface resistance, and this was more significant when the two materials were combined with lidocaine and distilled water.